UHPLC–Q-ToF-MS-guided enrichment and purification of triterpenoids from Centella asiatica (L.) extract with macroporous resin. Issue 1 (2nd January 2017) - Charles Dorni, A. I.; Peter, Gregary; Jude, Shintu; Arundhathy, C. A.; Jacob, Joby; Amalraj, Augustine; Pius, Anitha; Gopi, Sreeraj
ABSTRACT: The aim of the study is to standardize a simple and an effective extraction method for industrial preparation of Centella asiatica (L.) extract rich in triterpenoids. Macroporous resin purification process was adapted to enrich the triterpenes extracted from the herb. A sensitive analytical method with good resolution, linearity, and a shorter run time of 10 min was developed in ultra high-performance liquid chromatography–quadrupole-time-of-flight mass spectrometer for monitoring the triterpene (madecassoside, asiaticoside, madecassic acid, and asiatic acid) content at each stage of the extraction process. The standardized process could enrich the triterpene, madecassoside in the product up to a purity of 72.51% with overall recovery of the compound to 90.79%. A purified form of asiaticoside with a purity of 85% was obtained by dealcoholization and precipitation process exploiting the differential water solubility of the two major triterpenes. The binding and recovery of the aglycones (madecassic acid and asiatic acid) were observed to be poor, and hence the overall recovery of aglycones by this process was found to be very low. The purified triterpenoids were also confirmed by the 1 H NMR. Thus, the results suggest that the standardized process can be converted to industrial-scale preparation of high-value C. asiatica (L.) products rich in madecassoside or asiaticoside. GRAPHICAL ABSTRACT: